CHARGING FOR THE LAND IN THE CONTEXT OF THE IMPLEMENTATION OF THE STATE FINANCIAL CONTROL OF LAND RELATIONS - Ivanovа А.І. (The actual problems of regional economy development, 2018)
The article analyzes the structure of Ukrainian land and studies the structure of their changes. The problems of using land taxes in Ukraine as one of the methods of land relations regulation, the effectiveness of state support and the current state of taxation are determined. An estimation of the current state of land payment is made and the dynamics of tax revenues to the budget is analyzed. The existing problems in charging for land are determined. The conditions for optimization of tax revenues are formulated and the mechanism of application of taxation of land is proposed.